Produksi Biokompos Melalui Teknik Mini Biopori di dalam Wadah Bekas Ramah Lingkungan Untuk Tanaman Hortikultura - Dahliaty, Andi; Sophia, Halida; Azlina, Nur; Siregar, Siti Saidah; Susilawati, Susilawati; Nugroho, Titania Tjandrawati (Unri Conference Series: Community Engagement, 2024)
Mini biopori is an innovative and efficient technique for producing biocompost. This technique utilizes used containers that are environmentally friendly, allowing the community to independently process household organic waste. In addition to reducing waste, this technique also produces fertilizer that is beneficial for horticultural plants. The purpose of this community service activity is to provide knowledge and insights to the community about the application of mini biopori technology in used containers for horticultural plant production, enhance the community's skills in applying mini biopori technology, utilize the biocompost produced from biopori infiltration holes for planting horticultural crops, and assist the community from an economic aspect (increasing community income) by using simple and inexpensive materials to produce high-value horticultural plants. This activity is conducted in Sungai Berbari Village, Pusako District, Siak Regency. The methods of this community service consist of several stages, including preparation, training through lectures and discussions, practical implementation of the mini biopori technique, and evaluation, which considers the conditions before and after the training activities. The results of this activity indicate that the participants have a better understanding of the biocompost production process and the benefits of the mini biopori technique. All participants (100%) considered the mini biopore technique training to be very beneficial, indicating that this training has successfully provided added value to the participants. A total of 70% of the participants showed an interest in applying the mini biopore technique in their homes. The mini biopore technique is considered effective in managing organic waste, producing beneficial fertilizer, and has the potential to reduce dependence on chemical fertilizers. Additionally, implementing this technique can lower agricultural production costs, increase crop yields, and contribute to long-term economic well-being in the community.